DOP09 Eosinophils exert a pro-inflammatory role in a chronic DSS colitis model without an impact on fibrosis. (30th January 2023) - Jacobs, I; Deleu, S; Cremer, J; De Hertogh, G; Vermeire, S; Breynaert, C; Vanuytsel, T; Verstockt, B
Abstract: Background: Eosinophils might play a pro-inflammatory role in inflammatory bowel disease (IBD). However, the role of eosinophils in intestinal fibrosis remains poorly understood, although a pro-fibrotic function has been hypothesized based on data outside the gastrointestinal tract. Therefore, we aimed to unravel the role of eosinophils in chronic intestinal inflammation and fibrosis and to explore eosinophil depletion as a potential therapeutic target. Methods: A 3-cycles chronic dextran sodium sulphate (DSS) model was induced in 6-8-week-old C57BL/6 wild type mice. Mice received 3 DSS cycles (1.5% - 2.00% - 2.00%) in which 1 DSS cycle consisted of 1 week of DSS administration followed by 2 weeks of recovery. During the 3 cycles, and starting 3 days prior to colitis induction, anti-CCR3 antibody or isotype injections were given twice weekly to study the effect of the eosinophil depletion (total of 18 injections). The disease activity index (DAI; weight loss, stool consistency and presence of blood) was determined twice weekly. At sacrifice, colonic damage was scored macroscopically (presence of hyperaemia, adhesions and length and degree of colon affected by inflammation) and colonic single cells were isolated and fluorescently stained for flow cytometry. Eosinophils were thereby identified as CD45+ CD11b+ Siglec-F+ CD117- cells. Lastly, a histological active disease score was determined comprising of the sum of neutrophil infiltration, mononuclear cell infiltration, changes in mucosal architecture, goblet cell loss and epithelial defects (Creyns et al., 2019). Intestinal fibrosis was assessed via colon weight/length ratio, COL1A1 gene expression and collagen deposition with a Martius Scarlet Blue (MSB) staining and a colorimetric hydroxyproline assay. Results: Blood and colonic eosinophil depletion via anti-CCR3 injections was confirmed via flow cytometry (figure 1). The DAI in the eosinophil depleted group was decreased compared to the isotype injected group (area under the curve 115.4 ± 29 vs 160.6 ± 28; p=0.02). A similar trend was seen in the macroscopic damage score (2.0 ± 1.3 vs 3.9 ± 2.1; p=0.08). Furthermore, a lower histological active disease score was found in the mice in which the eosinophils were depleted compared to the isotype injected mice (8.8 ± 0.8 vs 12.8 ± 1.5; p=0.002) (figure 2). Lastly, no differences in the parameters for fibrosis between the anti-CCR3 injected and isotype injected groups were observed (figure 3). Conclusion: Eosinophil depletion via intraperitoneal anti-CCR3 injections resulted in partial protection from intestinal inflammation in chronic DSS, and could therefore be further explored as a potential therapeutic agent. In contrast, eosinophil depletion does not seem to have any anti-fibrotic effect